Integration of Arabic Language Curriculum and Character Education in Islamic Educational Institutions - Fathoni, Fathoni (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
This study aims to discuss the importance of integration between Arabic curriculum and character education in Islamic educational institutions. Arabic as the language of the Qur'an has a strategic value in the formation of Islamic character of students. Character education based on the noble values ​​of Islam can be strengthened through Arabic language learning that not only focuses on linguistic aspects, but is also full of moral and spiritual meaning. This study uses a descriptive qualitative approach with a literature study technique. The results of the study indicate that the integration of Arabic curriculum with character education can improve students' understanding of Islamic values, form noble morals, and strengthen their religious identity. This article recommends that Arabic teachers not only teach linguistic aspects, but also transform character values ​​through relevant learning materials and methods.